2017
DOI: 10.1111/pere.12191
|View full text |Cite|
|
Sign up to set email alerts
|

Transmission of ideas about love: Filial piety, love attitudes, and romantic satisfaction

Abstract: This study examined the relations between filial piety, attitudes about romantic relationships (love attitudes), and satisfaction in romantic relationships in the Chinese cultural context. The following research questions were investigated: How are adult children's filial piety beliefs connected to their love attitudes, and how do these contribute to their satisfaction in romantic relationships? A total of 412 college students in Taiwan who were currently involved or had been involved in romantic relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…However, gender difference in authoritarian FP was not statistically significant ( t = 0.37, p > 0.05, Cohen’s d = 0.04; Female: mean = 29.01, SD = 5.82; Male: mean = 28.80, SD = 5.17). These findings were consistent with previous research suggesting that females held stronger reciprocal FP than did Chinese males (Leung et al, 2010; Chen and Wu, 2017).…”
Section: Resultssupporting
confidence: 93%
“…However, gender difference in authoritarian FP was not statistically significant ( t = 0.37, p > 0.05, Cohen’s d = 0.04; Female: mean = 29.01, SD = 5.82; Male: mean = 28.80, SD = 5.17). These findings were consistent with previous research suggesting that females held stronger reciprocal FP than did Chinese males (Leung et al, 2010; Chen and Wu, 2017).…”
Section: Resultssupporting
confidence: 93%
“…Adding to the nuclear family-focused marital expectations ( Fletcher et al, 2000 ; Campbell et al, 2001 ; Simpson et al, 2002 ; Khazan et al, 2008 ; Seiger and Wiese, 2011 ), consistent with previous research results that filial piety could be proposed as an important virtue for mate preference ( Zhang and Kline, 2009 ; Jiang and Gong, 2015 ; Gui and Li, 2019 ), the present study found a culture-specific marital expectation under the extended family historical background and confirmed that young Chinese couples identify with filial virtue and evaluate their spouse’s filial piety toward their parents and that a higher evaluation implies higher marital satisfaction. The present study is different from Chen and Wu (2017) focus on the transmission of filial piety belief to “Storge and Agape” love attitudes. From Chen and Wu (2017) perspective, young people interacted with parents and with romantic partners similarly; the researchers did not take into account the conflict of interest between partner and parents, and thus the study did not include a comprehensive description of family interaction in reality.…”
Section: Discussionmentioning
confidence: 65%
“…The present study is different from Chen and Wu (2017) focus on the transmission of filial piety belief to “Storge and Agape” love attitudes. From Chen and Wu (2017) perspective, young people interacted with parents and with romantic partners similarly; the researchers did not take into account the conflict of interest between partner and parents, and thus the study did not include a comprehensive description of family interaction in reality. Considering conflicts of interest between spouse and parents, the current study’s result confirms the expectancy violations theory that a condition which matches one’s expectations leads to a satisfactory relationship ( Burgoon, 1993 ; Wu and Huang, 2012 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In Chen and Wu (), the authors wish to correct the affiliation of Chih‐Wen Wu to: Department of Human Development and Family Studies, National Taiwan Normal University…”
mentioning
confidence: 99%